When shared group membership signifies shared subjective experience: I-sharing and the minimal group paradigm. Issue 4 (4th July 2017) - Long, Anson E.; Pinel, Elizabeth C.; Yawger, Geneva C.
ABSTRACT: Ingroup favoritism is pervasive. It emerges even in the minimal group paradigm, where participants are assigned to novel groups based on seemingly insignificant characteristics. Yet many of the grouping schemes used in minimal group research may imply something significant: namely, that ingroup members will share in-the-moment subjective experience, or I-share . Two studies examine the role of inferred I-sharing in the minimal group paradigm. We found that (1) people inferred that they would I-share with ingroup members more than outgroup members; (2) inferred I-sharing increased ingroup favoritism; and (3) inferred I-sharing accounted for this ingroup favoritism. Moreover, expecting to I-share with the outgroup improved participants' attitudes toward the outgroup. These results converge with other research suggesting that people favor ingroup members, in part, because they expect to I-share with them.